2019
DOI: 10.1038/s41477-019-0510-0
|View full text |Cite
|
Sign up to set email alerts
|

COSY catalyses trans–cis isomerization and lactonization in the biosynthesis of coumarins

Abstract: Coumarins or 1,2-benzopyrones comprise a large class of secondary metabolites ubiquitously found in the plant kingdom. In many plant species, coumarins are particularly important for iron acquisition and plant defense. Here we show that COUMARIN SYNTHASE (COSY) is a key enzyme in the biosynthesis of coumarins. Arabidopsis thaliana cosy mutants are strongly reduced in coumarin levels and accumulate ohydroxyphenylpropanoids instead. Accordingly, cosy mutants have reduced iron content and show growth defects when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 49 publications
5
81
0
1
Order By: Relevance
“…However, this enzyme might contribute to umbelliferone synthesis in other species. An in vitro experiment demonstrated that AtCOSY is able to synthesize this FC precursor from 2,4‐dihydroxycinamoyl‐CoA (Vanholme et al ., ). The homologous genes of AtCOSY are conserved in various angiosperm taxa, including FC‐rich species, that is, fig, Angelica archangelica (Apiaceae), Bituminaria bituminosa (Fabaceae) and Citrus × paradisi (Rutaceae) (Murray et al ., ) (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, this enzyme might contribute to umbelliferone synthesis in other species. An in vitro experiment demonstrated that AtCOSY is able to synthesize this FC precursor from 2,4‐dihydroxycinamoyl‐CoA (Vanholme et al ., ). The homologous genes of AtCOSY are conserved in various angiosperm taxa, including FC‐rich species, that is, fig, Angelica archangelica (Apiaceae), Bituminaria bituminosa (Fabaceae) and Citrus × paradisi (Rutaceae) (Murray et al ., ) (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, a new gene encoding an enzyme catalysing trans‐cis isomerization and lactonization of o ‐hydroxycinnamoyl‐CoA (Vanholme et al ., ) was reported, which serves as an alternative route to the nonenzymatic process in coumarin skeleton formation (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the co‐cultivation of mutants defective in coumarin biosynthesis (e.g. f6′h1‐1 , cosy‐1 and cosy‐2 ) with WT plants was sufficient to rescue the mutant phenotypes (Rodriguez‐Celma et al ., 2013; Schmidt et al ., 2014; Vanholme et al ., 2019). In addition, chemical complementation experiments for f6′h1‐1 , s8h‐1 and s8h‐2 mutants showed that exogenous provision of coumarins (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In the light, 6-hydroxyferuloyl-CoA is converted into scopoletin, a reaction that occurs partially spontaneous. In light-protected organs such as roots, scopoletin biosynthesis is dependent on enzymatic catalysis via COUMARIN SYNTHASE (COSY) (Vanholme et al, 2019). Similar to F6’H1, COSY activity is indispensable for growth on alkaline substrates (Vanholme et al, 2019), suggesting that compounds which are produced downstream of scopoletin are required for the mobilization of Fe.…”
Section: Introductionmentioning
confidence: 99%